Florescence Intensity Ratio Thermometer in the First Biological Window Based on Non-Thermally Coupled Energy Levels of Tm3+ and Ho3+ Ions - Li, Liang; Hao, Haoyue (Frontiers in Materials, 2021)
In this study, the up-conversion luminescence and optical temperature sensing properties of Ho3+/Tm3+/Yb3+-co-doped NaLuF4 phosphors were investigated. The visible (475, 540, and 650 nm) and near-infrared light (692 and 800 nm) radiated from 1Ho3+/4Tm3+/Yb3+-co-doped NaLuF4 phosphors were obvious enough for subsequent detection. The slopes in the lnI–lnP plot of the emissions located in the first biological window (650, 692, and 800 nm) were both ∼1.5, which mean that the power had little effect on the three fluorescence peak ratios. Based on the florescence intensity ratios (FIRs) of 650 and 692 nm, the relative sensing sensitivity reaches 0.029 K−1 (476 K). The relative sensing sensitivity based on the FIRs of 800 and 692 nm reaches 0.0076 K−1 (476 K). The results reveal that 1Ho3+/4Tm3+/Yb3+-co-doped NaLuF4 phosphors have potential applications in FIR-based temperature sensing in biological tissue for their high sensing sensitivity. In addition, the emission colors of the sample stabilize in the white light region as the temperature increased from 303 to 467 K, implying that it can also be used in white display.